Features of Reforming Economic Legislation in the Conditions of Russian Aggression: Theoretical and Legal Aspects - SHEVCHENKO, Anatolii Y.; VYKHRYST, Serhiy M.; OSTAPENKO, Iuliia; BOBROVNYK, Svitlana V.; LOSHCHYKHIN, Oleksandr (Theoretical and Practical Research in Economic Fields; Vol 14 No 2 (2023): TPREF, Volume XIV, Issue 2(28), Winter 2023, 2023)
The aim of the article is to justify the inexpediency of the abolition of the Economic Code of Ukraine during martial law on the basis on the analysis of international legislation on management. Thus, the analysis of international codified acts on the economic sphere regulation shows that the abolition of the Economic Code of Ukraine does not correspond to the Concepts for updating civil and economic legislation as one of the ways of approximation of domestic legislation to international standards. Apart from that, based on the analysis of current Ukrainian and international legal acts, an attempt is made to explore the problems associated with the use of mechanisms for protecting rights to private property and bringing war criminals to justice for its destruction. Furthermore, the authors propose to improve the mechanisms for protecting the right to private property that is destroyed or damaged as a result of war crimes committed by Russian invaders on the territory of Ukraine. Finally, the authors highlight the key problems related to the restoration of the violated right to private property, which was destroyed or damaged as a result of hostilities on the part of Russia and emphasize the need to adopt international experience in order to increase the effectiveness of mechanisms for defending the violated right to property with the assistance of international legal institutions.